Chinese validation of “subjective motoric cognitive risk syndrome” screening tool in patients with coronary artery disease using Rasch analysis - Chai, Yiyi; Gu, Yanrong; Wu, Xiaomin; Wang, Yini; Lin, Ping; Ye, Qingfang; Li, Ling (Frontiers in Aging, 2025)
ObjectiveSubjective motoric cognitive risk syndrome (MCR-S) is a well-established screening tool that has been validated for objective motoric cognitive risk syndrome (MCR-O) and predicted risk of incident dementia. MCR is associated with cardiovascular factors and coronary artery disease (CAD). MCR-S is crucial for remote cognitive screening but has only been validated in community settings so far. Our study aimed to validate a Chinese version of the MCR-S in CAD patients.MethodThe Chinese version of the MCR-S was obtained through a standardized forward-backward translation and cultural adaptation. 338 CAD patients were recruited. Traditional analysis based on classical test theory and Rasch analysis based on latent trait theory were performed on the MCR-S for validation. Receiver operating characteristic analysis was applied to determine the discriminative ability of MCR-S for the MCR-O in CAD patients.ResultsThe MCR-S met the unidimensionality, lack of local dependency or disordered thresholds, and good fit value for each item of the Rasch model, the item-person map shows that the item’s estimate of capacity is appropriate. MCR-S has good content validity, criterion-related validity, and test-retest reliability. An optimal cut-score of 4.6 on the MCR-S score was determined to have good sensitivity (79.2%) and specificity (71.3%) for MCR-O in CAD patients.ConclusionThe Chinese version of MCR-S meets the requirements of the Rasch model and has good validity in CAD patients. The validated MCR-S cutoff can support long-term monitoring and early intervention for CAD patients at risk of MCR-O.